Pengaruh Kualitas Produk Terhadap Minat Beli Konsumen Pada Home Industri Pia Deisy Desa Kapitu Kecamatan Amurang Barat - Karundeng, Nikita; Kalangi, Johnny A. F.; Walangitan, Olivia F. C. (Sam Ratulangi University, 2019)
This study aims to determine whether Product Quality has an effect on Consumer Buying Interest. Speaking with quality and buying interest is certainly very tied to marketing. The essence of marketing according to Daryanto (2011)